Interleukin receptor family member ST2 concentrations in patients following heart transplantation. (May 2013) - Januzzi, James L.; Horne, Benjamin D.; Moore, Stephanie A.; Galenko, Oxana; Snow, Gregory L.; Brunisholz, Kimberly D.; Muhlestein, Joseph B.; Alharethi, Rami; Carlquist, John F.; Budge, Deborah; Rasmussen, Kismet; Kfoury, Abdallah G.
Abstract Objective: To evaluate soluble (s) ST2 as a biomarker of rejection, allograft vasculopathy and mortality after orthotopic heart transplantation (OHT). Methods: sST2 concentrations were measured in 241 patients following OHT. Results: Elevated sST2 was associated with cellular rejection (CR) ≥1R, with highest rates of CR in the 4th sST2 quartile (p = 0.003). No significant association between sST2 and antibody-mediated rejection or allograft vasculopathy was found. sST2 ≥30 ng/mL independently predicted death over 7-year follow-up (HR = 2.01; 95% CI 1.15–3.51; p = 0.01). Conclusion: Concentrations of sST2 are associated with the presence of CR and predict long-term mortality following OHT.